The Economic Implications of Terrorism in Developing Countries: Nigeria in Focus - Efebeh, Vincent Eseoghene; Johnson, Marvelous Otega (LPPM Universitas Malikussaleh, 2023)
The evil consequences of terrorism in our contemporary states have left so many countries of the world in a very serious economic crisis. The 9/11 terrorists attacks on the United States of America has changed the face of terrorism foe ever, especially to policy makers, academics and to publicists, leaving the human communities much more vulnerable than ever before. Worse hit are such countries with unstable governments most of which are in Africa. This paper examines the economic iniquitousness of terrorists conditioning in developing countries; particularly in Nigeria. The study adopted a historical method of data collection with a complete reliance on secondary data sources as obtained from books, magazines, academic journals, newspapers and the internet. The paper reveals that terrorists' attack had adversely affected the economies of developing countries; particularly, the Nigerian economic environment as it had drastically downshifted Foreign Direct Investment (FDI), the killing and maiming of unarmed citizenry who would have formed a formidable workforce for economic progress. The paper suggests that, economic activities can only thrive in an atmosphere of peace and tranquility, to that extent therefore, the government need to strengthen its collaborative efforts with her neighbours and other development partners across the world to curb the activities of the terrorists.